KERJASAMA ANTARA NOTARIS/PPAT DENGAN BANK YANG DITUANGKAN DALAM SUATU PERJANJIAN REKANAN - Putu Devi Yustisia Utami (Jurnal Hukum Saraswati (JHS), 2019)
Banks in providing credit, require the role of Notary/PPAT in the process of binding credit agreements and credit guarantees. Because of the increasing number of Notary/PPAT in some area, this cause more difficult for a Notary/PPAT to get clients. To overcome this, some Notaries/PPAT’s want to get many clients by collaborating with the banks, which is stated in a partnership agreement. When a Notary/PPAT becomes a partner of the bank, they will obtain job and client from the bank and binding themselves to the bank. The problems in this study are How is the existence of a partnership agreement between the Notary/PPAT with the bank reviewed from UUJN, Notary Code of Ethics and PPAT Regulation. This study used a normative legal research, with a Statute Approach and the Analytical Concept Approach. The legal materials are primary, secondary and tertiary legal materials.The conclusions in this stydy that the partnership between Notary/PPAT and the bank violates the provisions of article 16 paragraph 1 letter of the Law of The Notary and violates code of Ethics Notary and code of Ethics PPAT, as well as the partnership agreement between Notary/PPAT with the bank raises a contractual relationship between the Notary/PPAT and his client so that the Notary/PPAT can no longer carry out his position independently.